Analisis Komparatif Sistem Akumulasi Kos Proses dan Kos Pesanan Pada Es Teler Kayla dan Fotocopy Restu Bunda - Pipi Dwi Andira; Zulfa Aulia Salsabila; Annisa Istiqomah; Mellya Embun Baining (PADMA, 2026)
This study aims to conduct a comparative analysis of the application of process costing in the micro-enterprise Es Teler Kayla and job order costing in the micro-enterprise Fotocopy Restu Bunda, located in Sungai Duren, Muaro Jambi Regency. The research method employed is descriptive-comparative with a qualitative approach using interviews and documentation, enabling a realistic portrayal of business operations. The findings indicate that Es Teler Kayla is more suitable for process costing due to its homogeneous, repetitive, and mass daily production characteristics. In contrast, Fotocopy Restu Bunda is better suited for job order costing since its services depend on customer demand with varying specifications. The application of the appropriate costing method significantly improves the accuracy of production or service cost calculation and supports more precise pricing decisions. The contribution of this study lies in strengthening the understanding of cost accumulation methods within the context of micro, small, and medium enterprises (MSMEs), while also providing practical recommendations for small business owners to enhance cost management efficiency and competitiveness.